Visible Spectrophotometric Determination of Clarithromycin in Pharmaceutical Solid Dosage Forms - Srinivasa Rao, Y.; Rajani Kumar, V.; Seshagiri Rao, J.V.L.N. (Asian Journal of Chemistry, 2010)
A new simple visible spectrophotometric method is developed for the estimation of clarithromycin in pure and pharmaceutical dosage forms. The method is based on the reaction of the drug with marquis reagent, which forms a brown coloured chromogen with absorption maximum at 495 nm. The chromogen formed is stable and obeys Beer's law in the concentration range of 10–70 μg/mL.